CHILD ABUSE AMONG PARENTS IN EKITI STATE: IMPLICATION FOR GUIDANCE AND COUNSELLING - Olukoya Adewale Olotu (European Scientific Journal, ESJ, 2013)
The study examined various child abuse practices among parents in Irepodun/Ifelodun Local Government Area of Ekiti State. The purpose of the study was to find out the main cause(s) of child abuse and which form(s) of abuse is more prevalent in the state. Data was collected from two hundred children (male and female) below the age of 18 years old from Irepodun/Ifelodun L.G.A, using stratified random sampling. The instrument of the study was a self-constructed 40-item questionnaire. The validity of the instrument was established by face and content validity, while a test-retest method was employed to ascertain the reliability of the instrument, using Pearson product movement correlation equation to estimate the reliability co-efficient. The data were analyzed using frequency count and percentage. Chi-Square test was used to test all the hypotheses, at 0.05 alpha level of significance. The result showed that there was no significance difference between child abuse practices in urban and rural areas, polygamous and monogamous families. However, significant difference was found between literate and illiterate, intact and broken homes.